An analysis of the relationship between critical velocity and anaerobic speed reserve with match running profile in football - Cihan, H. (Pedagogy of Physical Culture and Sports, 2022)
Background and Study Aim. The aim of this study was to analyse the relationship between critical velocity (CV) and anaerobic speed reserve (ASR) with match running profile in football.